Participatory video project in Nepal - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
A group of 12 women from Dhanusha District, south Nepal, received three days video production training and shot their own stories about how climate change has affected their livelihoods. These pictures, documents the training and videoing process, including the participants' reactions to this new experience. The project was funded by The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), and organised by the International Water Management Institute (IWMI) in India. Photo: Pawan Kumar